3,5-Bis(4-fluorophenyl)isoxazole - Fun, Hoong-Kun (International Union of Crystallography, 2012)
In the crystal structure of the title compound, C(15)H(9)F(2)NO, the complete molecule is generated by a crystallographic twofold rotation axis and the O and N atoms of the central isoxazole ring are statistically disordered with equal site occupancies. The terminal benzene rings form a dihedral angle of 24.23 (3)° with the isoxazole ring. The dihedral angle between the benzene rings is 47.39 (2)°. No significant intermolecular interactions are observed.